Enhancing the mobility of collections and access to cultural heritage: immunity of cultural objects from seizure in Poland. Issue 3 (16th April 2019) - Gwoździewicz-Matan, Paulina; Jakubowski, Andrzej
Abstract: This paper analyses, from the perspective of cultural policy considerations, the legal regime established by the recent Polish law on the immunity from seizure of cultural property on loan (2015). It deals with current trends of international museum exchange and explains the benefits and risks involved in cross-border loans of cultural material. This analysis is carried out by focusing on the actual practice and experiences of Polish museums, national and international regulations in force, and human rights considerations. The authors attempt to situate the Polish model for the protection of foreign cultural property on loan within the broader comparative context of the domestic legislation on museum exchange adopted in selected national jurisdictions. The article also offers a more general cultural policy discussion in the context of international museum exchanges of cultural material. Laws and policies facilitating such exchanges are weighed against other rights and interests encompassed in the protection of cultural heritage and the realisation of all human rights, including cultural rights.